2006
DOI: 10.3748/wjg.v12.i2.322
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of angiotensin II receptor antagonist on hepatic stellate cell activation in non-alcoholic steatohepatitis

Abstract: Our data suggest the crucial involvement of HSCs in anti-fibrotic effect of angiotensin II receptor antagonist on patients with NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 22 publications
0
68
1
Order By: Relevance
“…In 2004, a clinical pilot study revealed the beneficial efficacy of losartan, one of the ARBs, against NASH by evaluating serum biochemical indices and hepatic histology [96]. Moreover, the effect of ARB on NASH was shown to be through the inhibition of activated hepatic stellate cells in NASH patients [97]. After this pilot study, many animal and in vitro studies confirmed the beneficial efficacy of ARBs against NASH, but clinical studies were very limited.…”
Section: Metformin Cq: Are Biguanides Effective For Patients With Nafmentioning
confidence: 84%
“…In 2004, a clinical pilot study revealed the beneficial efficacy of losartan, one of the ARBs, against NASH by evaluating serum biochemical indices and hepatic histology [96]. Moreover, the effect of ARB on NASH was shown to be through the inhibition of activated hepatic stellate cells in NASH patients [97]. After this pilot study, many animal and in vitro studies confirmed the beneficial efficacy of ARBs against NASH, but clinical studies were very limited.…”
Section: Metformin Cq: Are Biguanides Effective For Patients With Nafmentioning
confidence: 84%
“…The effects of Ang II on hepatic stellate cells (HSC) has been extensively studied (Bataller et al 2005(Bataller et al , 2003a(Bataller et al , b, 2000Wei et al 2001;Yokohama et al 2006;Zhang et al 2003), yet little information exists on the effect of Ang-(1-7) on these cells. Most studies using cell culture use culture medium supplemented with fetal calf serum (FCS) to encourage cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…AT-1 receptor antagonists including captopril, candesartan and losartan inhibit liver fibrosis in bile duct-ligated and CCl 4 treated rats (255)(256)(257). In human studies, it is suggested that AT-1 receptor antagonist can decrease the number of activated HSCs (258). A controlled pilot study in hepatitis C showed that losartan reduces liver fibrosis as compared to untreated controls (259) ET-1 is another vasoconstrictor that merits study.…”
Section: Modulation Of Vasoactivementioning
confidence: 99%